Effect of silicon-doped calcium phosphate cement on angiogenesis based on controlled macrophage polarization. (18th September 2021) - Lee, Soomin; Li, Zheng; Meng, Dehua; Fei, Qinming; Jiang, Libo; Fu, Tengfei; Wang, Ze; Liu, Shuhao; Zhang, Jian
Abstract: Vascularization is an important early indicator of osteogenesis involving biomaterials. Bone repair and new bone formation are associated with extensive neovascularization. Silicon-based biomaterials have attracted widespread attention due to their rapid vascularization. Although calcium phosphate cement (CPC) is a mature substitute for bone, the application of CPC is limited by its slow degradation and insufficient promotion of neovascularization. Calcium silicate (CS) has been shown to stimulate vascular endothelial proliferation. Thus, CS may be added to CPC (CPC–CS) to improve the biocompatibility and neovascularization of CPC. In the early phase of bone repair (the inflammatory phase), macrophages accumulate around the biomaterial and exert both anti- and pro-inflammatory effects. However, the effect of CPC–CS on macrophage polarization is not known, and it is not clear whether the effect on neovascularization is mediated through macrophage polarization. In the present study, we explored whether silicon-mediated macrophage polarization contributes to vascularization by evaluating the CPC–CS-mediated changes in the immuno-environment under different silicate ion contents both in vivo and in vitro . We found that the silicon released from CPC–CS can promote macrophage polarization into the M2 phenotype and rapid endothelial neovascularization during bone repair. Dramatic neovascularization and osteogenesis were observed in mouse calvarial bone defects implanted with CPC–CS containing 60% CS. These findings suggest that CPC–CS is a novel biomaterial that can modulate immune response, promote endothelial proliferation, and facilitate neovascularization and osteogenesis. Thus, CPC–CS shows potential as a bone substitute material.